Supramolecular binding material with underwater binding capacity and reversible binding capacity in air

By constructing a three-dimensional network structure through the reaction of short-cut carbon fibers with amino-dimethylsiloxane, the problems of underwater bonding and reversible bonding in air are solved, realizing a multifunctional bonding material with high strength, controllable peeling and self-healing, suitable for bonding needs in complex environments.

CN120923808APending Publication Date: 2025-11-11NINGBO INST OF TECH ZHEJIANG UNIV ZHEJIANG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511234236.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing bonding materials cannot bond underwater and lack reversible bonding capabilities, making it difficult to meet bonding requirements in complex environments, especially for the controlled peeling and non-destructive recycling of valuable or fragile samples.

Method used

Short-cut carbon fibers are surface-modified with isophorone diisocyanate and reacted with polydimethylsiloxane with amino groups at both ends to form a three-dimensional network structure with covalent bonds, hydrogen bonds and physical forces, achieving underwater bonding and reversible bonding in air, and the bonding strength can be controlled by infrared light irradiation.

Benefits of technology

It achieves an underwater bonding strength of 2.01 MPa and a reversible bonding strength of 2.6 MPa in air, and can withstand 5 cycles without degradation. It has controllable peeling and self-healing functions and is suitable for cross-material bonding of various materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120923808A_ABST
    Figure CN120923808A_ABST
Patent Text Reader

Abstract

The invention discloses a supramolecular binding material with underwater binding capacity and reversible binding capacity in air, which is characterized in that short carbon fiber is subjected to surface modification by isophorone diisocyanate to form an isocyanate active group, namely-N = C = O, and polydimethylsiloxane, namely NH-PDMS-NH, with two aminated ends is used as a polymer bridge chain; a bridging structure between carbon fibers is constructed through chemical reaction of amino and isocyanato, and finally preparation of the supramolecular binding material is achieved. The supramolecular polymer chain provides flexible and reversible hydrogen bond acting force and other physical acting force for material bonding to form a three-dimensional network through a covalent bond formed by reacting the tail end of the supramolecular polymer chain with a water molecular layer and hydroxyl on the surface of a substrate and a carbon fiber bridging structure for enhancing the mechanical property of the material structure; therefore, the supramolecular binding material has underwater binding capacity and reversible binding capacity in air. According to the invention, a solution is provided for bonding requirements in a complex environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of salient target detection technology, and in particular to supramolecular bonding materials with underwater and reversible air bonding capabilities. Background Technology

[0002] Adhesives and adhesives are widely used in daily life and industry. However, ordinary adhesives and adhesives cannot be directly applied underwater, and most lack reversible bonding capabilities after use, making them unusable. Secondly, existing underwater adhesives are still in the academic research stage, and their bonding performance mainly relies on non-covalent bonds. Most have bonding capabilities that cannot exceed the megapascal level, failing to meet practical application requirements. Furthermore, most adhesives and adhesives have a single function and lack stimulus-responsiveness. Therefore, after valuable or fragile samples have completed their bonding service, the interfacial adhesion force is difficult to actively control, hindering controllable peeling of the bonding interface and non-destructive sample recovery.

[0003] Traditional bonding materials, due to the limitations of their molecular structure, lack multifunctionality and cannot simultaneously possess the ability to bond underwater throughout the entire process and reversibly bond in air. This makes it difficult to meet the engineering application requirements of bonding in underwater environments and reversible bonding in air at the same time. Furthermore, after the bonding service ends, it is difficult to meet the application requirements of controlled peeling and non-destructive recycling of valuable or fragile samples. Summary of the Invention

[0004] To address the aforementioned shortcomings, this invention proposes a supramolecular bonding material with underwater and reversible air bonding capabilities, providing a solution for bonding needs in complex environments.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a supramolecular bonding material with underwater and reversible air bonding capabilities. The bonding material is made by modifying short-cut carbon fibers with isophorone diisocyanate to give the surface isocyanate active groups, i.e., -N=C=O. Aminated polydimethylsiloxane (NH2-PDMS-NH2) at both ends serves as the polymer bridge chain. A bridging structure between carbon fibers is constructed through the chemical reaction of amino groups and isocyanates. The supramolecular polymer chains form a three-dimensional network through covalent bonds formed by the reaction of their ends with water molecules and hydroxyl groups on the substrate surface, the carbon fiber bridging structure that enhances the mechanical properties of the material structure, hydrogen bonds that provide flexibility and reversibility for material bonding, and other physical forces. This enables the supramolecular bonding material to possess both underwater and reversible air bonding capabilities.

[0006] As an improvement, the supramolecular adhesive material has a maximum underwater bonding strength of 2.01 MPa and a maximum reversible bonding strength of 2.6 MPa in air, and can achieve at least 5 reversible bonding cycles in air without reducing its bonding performance.

[0007] As an improvement, supramolecular adhesive materials possess the ability to reduce adhesive strength through infrared light irradiation to achieve controlled peeling, thereby enabling controlled peeling and non-destructive recycling of valuable and fragile samples.

[0008] As an improvement, the chopped carbon fiber particles have a size of 200-500 mesh, and the polydimethylsiloxanes aminated at both ends have a molecular weight of 3000-5000.

[0009] As an improvement, the mass ratio of isophorone diisocyanate to chopped carbon fibers is 2:1-5:1, and the mass ratio of end-aminated polydimethylsiloxane to isophorone diisocyanate-modified carbon fiber polymer is 1:1-2:2.

[0010] As an improvement, the substrate includes, but is not limited to, metals, glass, ceramics, plastics, and low surface energy materials.

[0011] As an improvement, the preparation method of supramolecular adhesive materials includes the following steps: S1: An excess of isophorone diisocyanate is mixed with short-cut carbon fiber powder that has been washed and dried with ethanol to prepare an IPDI-CFP solution, so that sufficient isocyanate groups are grafted onto the surface of the short-cut carbon fiber, and the IPDI-CFP solution is rich in a large amount of free isophorone diisocyanate. S2: The IPDI-CFP solution is magnetically stirred for 10-30 min, followed by ultrasonic vibration for 10-30 min to generate IPDI-CFP polymer; S3: Add an organic solvent to the IPDI-CFP polymer, with the mass ratio of organic solvent to polymer being 5:1-20:1, to obtain an IPDI-CFP organic solution; S4: Slowly add aminated polydimethylsiloxane to the IPDI-CFP organic solution. The amino groups and isocyanates will be replaced to form a carbon fiber bridging structure, which will serve as the main framework of the supramolecular bonding material. S5: The mixture is magnetically stirred for 10-30 min and ultrasonically vibrated for 10-30 min to obtain a supramolecular bonding material.

[0012] As an improvement, organic solvents include tetrahydrofuran, ethanol, ethylene glycol, dichloromethane, or tetrachloromethane.

[0013] Compared with the prior art, the advantages of the present invention are as follows: In this invention, the bonding material is prepared from chopped carbon fibers, isophorone diisocyanate, and end-aminated polydimethylsiloxane. Through the synergistic effect of the chopped carbon fibers and the end-aminated polydimethylsiloxane (NH2-PDMS-NH2), a three-dimensional supramolecular network is constructed, combining covalent bonds, carbon fiber bridging structures, hydrogen bonds, and physical forces. The material acquires underwater adhesion capability (strength up to 2.01 MPa) by forming covalent bonds between the polymer ends and the water molecule layer / hydroxyl groups on the substrate surface, overcoming the bottleneck of underwater performance degradation in traditional materials. Hydrogen bonds and physical forces exhibit reversibility, enabling reversible bonding in air (strength 2.6 MPa, no decay after at least 5 cycles). Combined with a carbon fiber bridging structure, the material's mechanical properties are significantly improved, with a substantial increase in impact toughness while maintaining structural stability. Furthermore, the infrared absorption characteristics of carbon fibers, combined with the thermal responsiveness of the supramolecular polymer chains, allow for controllable adjustment of bond strength through infrared irradiation. Shortened carbon fibers absorb infrared light, causing localized heating and weakening hydrogen bond forces, resulting in a controllable reduction in bond strength. This enables controlled peeling and non-destructive recycling of valuable samples. Moreover, the reversible breakage and recombination of supramolecular hydrogen bonds under heating conditions endow the material with potential self-healing capabilities, extending its service life. This achieves a breakthrough in multi-dimensional bonding performance, overcoming the performance limitations of traditional materials in complex environments while being suitable for reusable applications. Additionally, this supramolecular bonding material overcomes the bonding challenges of traditional bonding materials with low surface energy materials such as PTFE and silicone rubber, achieving excellent cross-material bonding capabilities across metals, ceramics, plastics, and composite materials, expanding its application potential in various material joining fields.

[0014] The matching of 200-500 mesh short-cut carbon fiber particle size with 3000-5000 molecular weight of NH2-PDMS-NH2 ensures material homogeneity and reactivity. Precise control of the mass ratio of isophorone diisocyanate (IPDI) to carbon fiber (2:1-5:1) and the mass ratio of NH2-PDMS-NH2 to IPDI-modified carbon fiber (1:1-2:2) balances reaction efficiency and material properties. The strategy of using excess isophorone diisocyanate during preparation ensures sufficient grafting of isocyanate ions (-N=C=O) onto the carbon fiber surface, while free isophorone diisocyanate in the solution participates in subsequent reactions, increasing the density of the bridging structure. Slow dropwise addition of NH2-PDMS-NH2 avoids excessively rapid local reactions leading to structural inhomogeneity, ensuring uniform supramolecular network formation. Synergistic magnetic stirring and ultrasonication promote IPDI-CFP polymer dispersion and reaction homogeneity, improving material consistency. Attached Figure Description

[0015] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments: Figure 1 This is a flowchart of the preparation process of supramolecular binders; Figure 2 This diagram illustrates the reaction process between the components during the preparation of supramolecular binders. Figure 3 This is a schematic diagram of the molecular structure of a supramolecular binder; Figure 4 This is a diagram showing the entire underwater bonding process of the supramolecular binder prepared in Example 1 to the iron weight; Figure 5 The following are the adhesion diagrams of the supramolecular binder prepared in Example 1 to various materials; Figure 6 The diagram shows the underwater bonding performance of the supramolecular binder prepared in Example 1 to different materials. Figure 7 The graph shows the adhesion properties of the supramolecular binder prepared in Example 1 to different materials in air. Figure 8 The supramolecular binder prepared in Example 1 was subjected to multiple cyclic bonding tests on an iron surface in air; Figure 9 This is a diagram showing the bonding failure process of the supramolecular binder prepared in Example 1 under infrared light irradiation. Detailed Implementation

[0016] Example 1 like Figures 1 to 2 As shown, the preparation method of supramolecular bonding materials includes the following steps: S1: 0.45g of isophorone diisocyanate and 0.254g of short-cut carbon fiber powder with a particle size of 300 mesh, which has been washed and dried with ethanol, are mixed to prepare IPDI-CFP solution, so that sufficient isocyanate groups are grafted onto the surface of the short-cut carbon fiber, and the IPDI-CFP solution is rich in a large amount of free isophorone diisocyanate. S2: The IPDI-CFP solution was magnetically stirred for 10 min, followed by ultrasonic vibration for 20 min to generate IPDI-CFP polymer; S3: Add 12 g of the organic solvent tetrahydrofuran to the IPDI-CFP polymer to prepare an IPDI-CFP organic solution; S4: Slowly add 12 g of polydimethylsiloxane with a molecular weight of 3000 to the IPDI-CFP organic solution. The amino groups and isocyanates will be replaced to form a carbon fiber bridging structure, which will serve as the main framework of the supramolecular bonding material. S5: The mixture was magnetically stirred for 10 min and ultrasonically vibrated for 20 min to obtain a supramolecular bonding material.

[0017] like Figure 3As shown, the molecular structure of the prepared supramolecular bonding material mainly includes inter-carbon fiber bridging structures and flexible polymer chains.

[0018] The supramolecular underwater adhesive in this embodiment was tested using a tensile testing machine. The adhesive curing time was 20 hours, the temperature was room temperature (25°C), and the adhesion test method was a vertical adhesion test. (1) First, a water bonding performance test was conducted. The underwater bonding was first verified using an iron weight as an example. Figure 4 As shown, this supramolecular adhesive can bond iron weights underwater throughout the entire process, proving that the present invention can achieve underwater bonding. Figure 5 As shown, this supramolecular underwater adhesive is also applicable to other materials, proving that the present invention can be used with a variety of materials when exerting underwater bonding performance.

[0019] Using the supramolecular bonding material in this embodiment, underwater bonding tests were conducted on various materials, and the test results are as follows: Figure 6 As shown in the table below, the underwater bonding strength to glass is the highest, approximately 2 MPa, while the bonding strength to polytetrafluoroethylene (PTFE) is the lowest. Specific test results are as follows: (2) Then, an air adhesion test was conducted. Using the supramolecular adhesive material in this embodiment, an air adhesion test was performed on various materials. The test results are as follows: Figure 7 As shown in the table below, the underwater bonding strength to glass is the highest, approximately 2.5 MPa, while the bonding strength to polytetrafluoroethylene (PTFE) is the lowest. Specific test results are as follows: Furthermore, taking iron as an example, a cyclic adhesion test was conducted to verify its reversible adhesion in air. The sample interface that failed to adhere after the first test was reattached and placed in a temperature-controlled chamber at 75 ℃ for 10 minutes. Then it was moved to room temperature and kept for 30 minutes to allow it to return to room temperature before a second adhesion test was conducted.

[0020] This process was repeated 5 times, and the resulting bonding properties were tested as follows: Figure 8 As shown, the results indicate that after 5 cycles of bonding, the bonding strength did not decrease and remained at around 1.5 MPa, proving that the adhesive involved in this invention has reversible bonding properties in air.

[0021] The specific test results are as follows: the first bond strength is 1496 ± 160 kPa (i.e., 1.496 ± 0.16 MPa), the second bond strength is 1780 ± 1100 kPa (i.e., 1.78 ± 0.11 MPa), the third bond strength is 1462 ± 147 kPa (i.e., 1.462 ± 0.147 MPa), the fourth bond strength is 1445 ± 327 kPa (i.e., 1.445 ± 0.327 MPa), and the fifth bond strength is 1490 ± 349 kPa (i.e., 1.49 ± 0.349 MPa).

[0022] (3) Conduct infrared response adhesion tests in air, such as Figure 9 As shown, the bond strength of the adhered iron weights decreased under infrared light irradiation, leading to bond failure, proving that the supramolecular adhesive of this invention exhibits infrared responsiveness in its bonding performance. Using iron as the test sample, the changes in bonding performance under different power infrared light irradiation were tested. The results show that the bonding strength decreases rapidly with increasing light power, confirming that the adhesive involved in this invention exhibits infrared responsiveness in its bonding performance. Specific test results are shown in the table below: In summary, the overall performance of the supramolecular binder prepared in this embodiment can be summarized as follows: Example 2 The weight of isophorone diisocyanate in S1 is 0.9g; The remaining steps are the same as in Example 1, so they will not be repeated here.

[0023] The supramolecular underwater adhesive in this implementation example was tested using a tensile testing machine. The curing time of the adhesive material was 20 hours, the temperature was room temperature (25°C), and the adhesion test method was a vertical adhesion test. The adhesion performance of the supramolecular adhesive prepared in this embodiment was tested. It showed the greatest adhesion performance to glass, with a maximum underwater adhesion strength of 1.976 MPa and a maximum air adhesion strength of 3.65 MPa.

[0024] Example 3 The weight of isophorone diisocyanate in S1 is 0.3g; The remaining steps are the same as in Example 1, so they will not be repeated here.

[0025] The supramolecular underwater adhesive in this implementation example was tested using a tensile testing machine. The curing time of the adhesive material was 20 hours, the temperature was room temperature (25°C), and the adhesion test method was a vertical adhesion test. The adhesion performance of the supramolecular adhesive prepared in this embodiment was tested. It showed the greatest adhesion performance to glass, with a maximum underwater adhesion strength of 1.81 MPa and a maximum air adhesion strength of 1.926 MPa.

[0026] Example 4 The weight of isophorone diisocyanate in S1 is 0.225 g, and the weight of short-cut carbon fiber is 0.127 g. The remaining steps are the same as in Example 1, so they will not be repeated here.

[0027] The supramolecular underwater adhesive in this implementation example was tested using a tensile testing machine. The curing time of the adhesive material was 20 hours, the temperature was room temperature (25°C), and the adhesion test method was a vertical adhesion test. The adhesion performance of the supramolecular adhesive prepared in this embodiment was tested, and it showed the greatest adhesion performance to glass, with a maximum underwater adhesion strength of 0.6307 MPa and a maximum air adhesion strength of 0.6947 MPa.

[0028] Example 5 The weight of isophorone diisocyanate in S1 is 0.45g, and the weight of short-cut carbon fiber is 0.05g. The remaining steps are the same as in Example 1, so they will not be repeated here.

[0029] The supramolecular underwater adhesive in this implementation example was tested using a tensile testing machine. The curing time of the adhesive material was 20 hours, the temperature was room temperature (25°C), and the adhesion test method was a vertical adhesion test. The adhesion performance of the supramolecular adhesive prepared in this embodiment was tested. It showed the greatest adhesion performance to glass, with a maximum underwater adhesion strength of 1.938 MPa and a maximum air adhesion strength of 2.367 MPa.

[0030] The effect of isophorone diisocyanate (IDI) addition on the bond strength of supramolecular binders was analyzed. Examples 1, 2, and 3 were compared sequentially, with IDI addition amounts of 0.3 g, 0.45 g, and 0.9 g, respectively. The corresponding maximum underwater and air bond strengths are shown in the table below. The results show that with increasing IDI, the maximum underwater bond strength changes relatively little, remaining around 1800-2400 MPa. However, with increasing IDI, the maximum air bond strength changes significantly, increasing from 1.926 MPa to 3.65 MPa.

[0031] Analysis of the results from the examples shows that as the isophorone diisocyanate content increases, the isocyanate density inside the adhesive continuously increases, significantly affecting the final bond strength in air. However, due to the influence of the underwater environment, the isocyanate density inside the adhesive has a smaller impact on the underwater bond strength.

[0032] The effect of chopped carbon fiber addition on the bonding strength of supramolecular adhesive was analyzed. Examples 1 and 5 were compared sequentially, with chopped carbon fiber additions of 0.254 g and 0.05 g, respectively. The corresponding maximum underwater bonding strength, air bonding strength, and infrared responsiveness are shown in the table below. The results show that the amount of chopped carbon fiber added slightly affects the bonding strength. As the amount of chopped carbon fiber added decreases from 0.254 g to 0.05 g, the maximum underwater bonding strength slightly decreases from 2.105 ± 0.376 MPa to 1.938 MPa, and the maximum air bonding strength slightly decreases from 2.63 ± 0.7 MPa to 2.367 MPa. These results indicate that a small amount of chopped carbon fiber is sufficient to achieve a carbon fiber bridging structure. However, when the amount of chopped carbon fiber added decreases from 0.254 g to 0.05 g, the bonding performance of the supramolecular adhesive loses its infrared responsiveness. Therefore, to ensure the infrared responsiveness of the supramolecular adhesive, a sufficient amount of chopped carbon fiber must be ensured during its preparation.

[0033] The above description only illustrates the preferred embodiments of the present invention and should not be construed as limiting the scope of the claims. The present invention is not limited to the above embodiments, and variations in its specific structure are permitted. All modifications made within the scope of the independent claims of this invention are also within the scope of protection of this invention.

Claims

1. A supramolecular bonding material with reversible underwater and air bonding capabilities, characterized in that: The bonding material is made by modifying short-cut carbon fibers with isophorone diisocyanate to give the surface isocyanate active groups, i.e., -N=C=O. It uses aminated polydimethylsiloxane (NH2-PDMS-NH2) at both ends as polymer bridge chains. A bridging structure between carbon fibers is constructed through the chemical reaction of amino groups and isocyanates. The supramolecular polymer chains form a three-dimensional network through covalent bonds formed by the reaction of their ends with water molecules and hydroxyl groups on the substrate surface, the carbon fiber bridging structure that enhances the mechanical properties of the material structure, hydrogen bonds that provide flexibility and reversibility for bonding, and other physical forces. This gives the supramolecular bonding material underwater bonding capability and reversible bonding capability in air.

2. The supramolecular bonding material with underwater bonding and reversible air bonding capabilities according to claim 1, characterized in that: The supramolecular adhesive material has a maximum underwater bonding strength of 2.01 MPa and a maximum reversible bonding strength of 2.6 MPa in air, and can achieve at least 5 reversible bonding cycles in air without reducing its bonding performance.

3. The supramolecular bonding material with underwater bonding and reversible air bonding capabilities according to claim 1, characterized in that: The supramolecular adhesive material has the ability to reduce the adhesive strength through infrared light irradiation to achieve controlled peeling, thereby enabling controlled peeling and non-destructive recycling of valuable and fragile samples.

4. The supramolecular bonding material with underwater and reversible air bonding capabilities according to claim 1, characterized in that: The chopped carbon fiber particles have a size of 200-500 mesh, and the polydimethylsiloxane with amino groups at both ends has a molecular weight of 3000-5000.

5. The supramolecular bonding material with underwater bonding and reversible air bonding capabilities according to claim 1, characterized in that: The mass ratio of isophorone diisocyanate to chopped carbon fibers is 2:1-5:1, and the mass ratio of the end-aminated polydimethylsiloxane to the isophorone diisocyanate-modified carbon fiber polymer is 1:1-2:

2.

6. The supramolecular bonding material with underwater and reversible air bonding capabilities according to claim 1, characterized in that: The substrate includes, but is not limited to, metals, glass, ceramics, plastics, and low surface energy materials.

7. The supramolecular bonding material with underwater and reversible air bonding capabilities according to claim 1, characterized in that: The preparation method of the supramolecular bonding material includes the following steps: S1: An IPDI-CFP solution is prepared by mixing an excess of isophorone diisocyanate with chopped carbon fiber powder that has been washed and dried with ethanol, so that sufficient isocyanate groups are grafted onto the surface of the chopped carbon fiber, and the IPDI-CFP solution is rich in a large amount of free isophorone diisocyanate. S2: The IPDI-CFP solution is magnetically stirred for 10-30 min, followed by ultrasonic vibration for 10-30 min to generate IPDI-CFP polymer; S3: Add an organic solvent to the IPDI-CFP polymer, with the mass ratio of organic solvent to polymer being 5:1-20:1, to obtain an IPDI-CFP organic solution; S4: Slowly add aminated polydimethylsiloxane to the IPDI-CFP organic solution. The amino groups and isocyanates will be replaced to form a carbon fiber bridging structure, which will serve as the main framework of the supramolecular bonding material. S5: The mixture is magnetically stirred for 10-30 min and ultrasonically vibrated for 10-30 min to obtain a supramolecular bonding material.

8. The supramolecular bonding material with underwater bonding and reversible air bonding capabilities according to claim 7, characterized in that: The organic solvents include tetrahydrofuran, ethanol, ethylene glycol, dichloromethane, or tetrachloromethane.